Meningkatkan Hasil Belajar Siswa Pada Materi Sumber Daya Alam Dan Kegiatan Ekonomi Dengan Menggunakan Media Peta Dan Gambar Serta Metode Diskusi di Kelas IV SDN Rawalumbu - Agus Krisdiyanto (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This research we conducted with the aim to improve the learning achievementsof students in muatan Social Science lessons natural resources and economic activities in grade IV semester 2 sd Negeri Rawalumbu, Researchers use discussion and observation methods as well as media maps and images as an effort to achieve that goal. From the identification of good data from the observation of learning activities in cycle I, it still has not produced satisfactory results. This can be seen from the average achievement of students who are still under KKM which is 69.28. While skor learning activityis 70.45. In cycle II, theaverage student learning achievement result increasedabove KKM to 77.86. While skor learning activitiesbecame 93.18. Based on the analysis of data in cycles I and II it was concluded that the use of discussion and observation methods as well as map and image mediaimprovedstudents' learning achievements in ips lessons in Natural Resources and Economic Activities.